Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/978-3-642-55122-2_109
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Human Capital Investment on Firm Performance: An Empirical Study of Chinese Industrial Firms

Abstract: As the technological innovation becomes the vitality of enterprise development, firms are increasingly realizing that, employees' knowledge and skills are the unique resources to gain the competitive advantages. Human capital is becoming the driving force to promote the enterprise development. Using data from Chinese Industrial Enterprises Database, this paper examines how human capital investment (including education and training investment) affects the firm performance. The results show that, employees' educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…Based on the findings, human capital had a positive and significant impact on bank performance; therefore, hypothesis H1 is supported. The results are also consistent with previous studies (Li et al , 2014; Kor and Leblebici, 2005; Maditinos et al , 2011) and the RBV theory. Therefore, efficient utilization of human capital will positively impact bank performance, which further stresses the importance of knowledge-based resources to a firm's competitive advantage, particularly service organizations like banks.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Based on the findings, human capital had a positive and significant impact on bank performance; therefore, hypothesis H1 is supported. The results are also consistent with previous studies (Li et al , 2014; Kor and Leblebici, 2005; Maditinos et al , 2011) and the RBV theory. Therefore, efficient utilization of human capital will positively impact bank performance, which further stresses the importance of knowledge-based resources to a firm's competitive advantage, particularly service organizations like banks.…”
Section: Resultssupporting
confidence: 93%
“…Extant literature shows that human capital plays a critical role in firm innovativeness and customer satisfaction (Bornay-Barrachina et al , 2017; Aryee et al , 2016). While some studies have also linked an organization's investment in human capital to improve firm value and profitability (Hejazi et al , 2016; Li et al , 2014). Therefore, a firm's expenditures on employees should be viewed as an investment rather than costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Firms with relatively more educated owners are found to perform better in terms of sales and profits and are likely to have better survival rates (Fairlie and Robb 2008). Moreover, empirical evidence has shown that the educational levels of employees have a statistically significant and positive effect on firm growth (Li et al 2014). …”
Section: Resultsmentioning
confidence: 99%
“…This metric measures the change in financial resources allocated to acquiring, implementing, and maintaining cloud computing infrastructure, platforms, and software applications. It encompasses various expenses associated with cloud technology adoption, including subscription fees for cloud services, investments in infrastructure as a service (IaaS), platform as a service (PaaS), and software as a service (SaaS) solutions, as well as costs related to cloud migration, training, and support services (Li et al, 2020). Cloud Expenditure Growth reflects the organization's commitment to using cloud computing strategically to achieve business objectives such as enhancing operational efficiency, scalability, and agility, potentially while reducing upfront capital expenditures and total cost of ownership compared to traditional on-premise IT infrastructure.…”
Section: Cloud Expenditure Growthmentioning
confidence: 99%